2015
DOI: 10.14689/ejer.2015.59.10
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Teachers' Perception about School Managers' Talent Management Leadership and the Level of Organizational Commitment

Abstract: Problem statement: Talent Management (TM) has been recently seen as a critical success factor in the development of educational organizations. The problem this study addresses is whether there is a relationship between teacher perceptions about school managers' TM leadership and their level of organizational commitment (OC). The level of school managers' TM leadership characteristics could influence the teachers' OC either positively or negatively. Within this context, in this study, great importance is attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
2
18
0
11
Order By: Relevance
“…In light of such startling findings, principal leadership style is important to recruiting and retaining teachers. A multitude of studies solidify the belief that leaders' behavior and staff perception have statistically significant correlation positively impacting job satisfaction and long term retention (Allen, 2015;Anderson, 2015;Aytaç, 2015;Bonaros, 2006;Boyce & Bowers, 2018;Gupta, 2015;McKinney, 2009;Owens, 2013;Yeldell, 2012;Zhang, 2010). Leadership is as much about leaders' behaviors as it is about followers' perception of the leader (Arogundade & Arogundade, 2015).…”
Section: Perceptions Of School Leader Effectivenessmentioning
confidence: 96%
“…In light of such startling findings, principal leadership style is important to recruiting and retaining teachers. A multitude of studies solidify the belief that leaders' behavior and staff perception have statistically significant correlation positively impacting job satisfaction and long term retention (Allen, 2015;Anderson, 2015;Aytaç, 2015;Bonaros, 2006;Boyce & Bowers, 2018;Gupta, 2015;McKinney, 2009;Owens, 2013;Yeldell, 2012;Zhang, 2010). Leadership is as much about leaders' behaviors as it is about followers' perception of the leader (Arogundade & Arogundade, 2015).…”
Section: Perceptions Of School Leader Effectivenessmentioning
confidence: 96%
“…In seven studies examined, there are findings revealing a significant and positive relationship between continuance commitment and different leadership behaviors (Arabacı, Alanoğlu & Doğan, 2014;Aytaç, 2015;Bozkuş & Gündüz, 2016;Çetin & Aydın, 2012;Çokluk & Yılmaz, 2010;Doğan & Aslan, 2016). They reported that there were significant and positive relationships between supportive leadership, servant leadership, spiritual leadership, talent management dimensions of strategic talent and working with others and continuance commitment, and between charismatic leadership, ethics in decision-making, transformational leadership dimensions of inspirational motivation, individual interest and intellectual stimulation and continuance commitment.…”
Section: Relationships With Continuance Commitmentmentioning
confidence: 99%
“…İncelenen yedi farklı çalışmada devam bağlılığı ile liderlikte farklı davranışların anlamlı ve pozitif yönde ilişkileri olduğuna dair bulgular bulunmaktadır (Arabacı, Alanoğlu ve Doğan, 2014;Aytaç, 2015;Bozkuş ve Gündüz, 2016;Çetin ve Aydın, 2012;Çokluk ve Yılmaz, 2010;Doğan ve Aslan, 2016). Destekleyici liderlik, hizmetkar liderlik ruhsal liderlik, yetenek yönetimi liderliği boyutlarından stratejik yetenek ve başaklarıyla birlikte çalışma ile devam bağlılığı arasında ve karizmatik liderlik, karar vermede etik ve dönüşümcü liderlik boyutlarından ilham verici motivasyon, bireysel ilgi ve entelektüel uyarım ile devam bağlılığı arasında anlamlı ve pozitif yönde ilişkiler olduğu bulunmuştur.…”
Section: Devam Bağlılığı Ile İlgili İlişkilerunclassified
“…Bunun nedeni öğretim kademelerinin farklı olması şeklinde açıklanabilir. Diğer taraftan ortaöğretim kurumlarında, Aytaç (2015) tarafından yapılan bir araştırmada öğretmen algılarına göre okul yöneticilerinin yetenek yönetimi liderliği düzeyleri orta olarak bulunmuş aynı zamanda Demirkasımoğlu ve Taştan (2015) özel öğretim kurumlarında yetenek yönetimi uygulamalarının "orta" düzeyde olduğunu belirlemişlerdir. Bu bulgular ile araştırma bulguları oldukça benzerlik göstermektedir.…”
Section: Sonuç Ve Tartişmaunclassified